Histological Bone-Healing Evaluation of Critical-Size Defects Filled with β-Tricalcium Phosphate in Rat Tibiae - Vasques, Ana Maria Veiga [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; Guimarães, Maria Rosa Felix de Souza Gomide; Valentim, Diego [UNESP]; da Silva, Ana Cláudia Rodrigues [UNESP]; Benetti, Francine; Santos, João Miguel Marques; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (MDPI, 2024)
Bone defects may be a result of different pathologies and represent a challenge in different fields of dentistry. Techniques for the correction of bone defects involving the use of several types of grafts have been proposed. This study evaluated bone repair in rat tibiae after surgically created critical-size defects were filled with β-tricalcium phosphate (RTR®, Septodont, FR). Critical-size bone defects were created in the tibiae of 32 male Wistar rats, which were divided into four groups (n = 8): Control 30 days, Control 90 days, RTR® 30 days, and RTR® 90 days. After the experimental period, the animals were euthanized and specimens were collected, embedded in paraffin, serially cut, and stained with hematoxylin and eosin to evaluate the inflammatory and repair response. Two parameters were analyzed: neoformed bone tissue areas (NBA) and neoformed cortical areas (NCA). Statistical analysis was performed by ANOVA and Tukey’s test (p < 0.05). The RTR® group demonstrated superior bone healing compared with the control group in both analyzed parameters (NBA and NCA), with repair of the cortical bone and bone-tissue formation in the central region of the defect, which showed partial repair in the defect area (p < 0.05). RTR® enhanced bone neoformation in the adopted experimental model and may be a useful biomaterial to boost healing in cases of critical-size bone defects.
Keywords: bone regeneration; bone substitute; RTR®; β-tricalcium phosphate